2013
DOI: 10.2141/jpsa.0120150
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Two Types of Glycated Tryptophan Compounds in the Plasma of Chickens Fed Tryptophan Excess Diets

Abstract: When tryptophan is glycated with glucose, it results in forming two types of glycated tryptophan compounds, glucose-tryptophan Amadori product and (1R, 3S) -1-(D-gluco-1, 2, 3, 4, 5-pentahydroxypentyl) -1, 2, 3, 4-tetrahydro-β-carboline-3-carboxylic acid (PHP-THβC). As hyperglycemia and high body temperature are the characteristics in avian species, these are supposed to elevate the concentration of glycated tryptophan compounds in the plasma of chickens. However, there was no attempt to detect two types of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Previously, we successfully detected two types of glycated tryptophan compounds in the chicken plasma, but did not clearly distinguish glucose-tryptophan Amadori product from PHP-THβC (Kita et al, 2013). In the present study, as shown in Table 4, glucose-tryptophan Amadori product and PHP-THβC could be successfully detected in the plasma.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Previously, we successfully detected two types of glycated tryptophan compounds in the chicken plasma, but did not clearly distinguish glucose-tryptophan Amadori product from PHP-THβC (Kita et al, 2013). In the present study, as shown in Table 4, glucose-tryptophan Amadori product and PHP-THβC could be successfully detected in the plasma.…”
Section: Discussioncontrasting
confidence: 64%
“…Because of hyperglycemia and high temperature in avian species, glycation of glucose and tryptophan has to be easily proceeded compared to mammals (Klandorf et al, 1995;Iqbal et al, 1999). Recently, we have detected two types of glycated tryptophan compounds in the plasma of chickens fed tryptophan excess diets (Kita et al, 2013). But, in our previous study, glucose-tryptophan Amadori product and PHP-THβC were not identified separately.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, it has not been elucidated whether Amadori products (glycated amino acids), which are the precursors of AGEs, can be also incorporated into cells or not. Previously, we could successfully synthesize Amadori products from glucose and tryptophan, and measured the plasma concentrations of glycated-tryptophan (Kita et al, 2013;Makino et al, 2015). Furthermore, we have been able to synthesize glycated-valine (Takahashi and Kita, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The protocol used to remove protein and lipid from plasma samples was based on a previous report by Kita et al (2013), with small modification. Briefly, before deproteinization and delipidation, 62.5 μL of 0.33 mM N-α-acetyl-L-tryptophan (Watanabe Chemical Industries, Ltd., Hiroshima, Japan) was added into 500 μL of plasma as internal standard.…”
Section: Deproteinization and Delipidation Of Plasma Samplesmentioning
confidence: 99%